Learn more: Show what you know - Bergin, David; Bergin, Christi Crosby; Van Dover, Teresa; Murphy, Bridget (Phi Delta Kappan, 2013)
The authors argue that the prospect of performance can motivate students to learn. He uses a study of the Above and Beyond program at a K-5 school, where students appeared to be more interested in their subjects and learn more effectively when given the opportunity to display or perform in front of an audience.